1996
DOI: 10.1074/jbc.271.16.9579
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenesis Studies of Interleukin-8

Abstract: Interleukin-8 (IL-8) is a dimeric, C-X-C chemokine, produced by a variety of cells and which elicits proinflammatory responses from the neutrophil. As a prelude to drug design, we have investigated the interactions between IL-8 and its receptor by preparing a number of single-site mutants of IL-8 and determining their activity in receptor-binding and functional assays. In order to define the binding surface as precisely as possible, we have used chemical shifts obtained from nuclear magnetic resonance spectros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0

Year Published

1996
1996
2003
2003

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(44 citation statements)
references
References 37 publications
3
40
0
Order By: Relevance
“…Chemokines are divided into four families based on the pattern of cysteine residues (C, CC, CXC, and CX 3 C), and they exert their effects by binding and signaling through seven transmembrane G protein-coupled receptors (GPCRs) on the surface of leukocytes. Although the molecular details remain unclear, mutagenesis and NMR studies have revealed some of the structural requirements for receptor binding and activation (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). Collectively, these studies support a hypothesis whereby chemokines activate their receptor through a putative two-step mechanism.…”
Section: T He Directed Migration Of Leukocytes Into Areas Of Inflammasupporting
confidence: 61%
See 2 more Smart Citations
“…Chemokines are divided into four families based on the pattern of cysteine residues (C, CC, CXC, and CX 3 C), and they exert their effects by binding and signaling through seven transmembrane G protein-coupled receptors (GPCRs) on the surface of leukocytes. Although the molecular details remain unclear, mutagenesis and NMR studies have revealed some of the structural requirements for receptor binding and activation (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). Collectively, these studies support a hypothesis whereby chemokines activate their receptor through a putative two-step mechanism.…”
Section: T He Directed Migration Of Leukocytes Into Areas Of Inflammasupporting
confidence: 61%
“…Arginine at position 24 is also highly conserved among MCPs and resides within a 3 10 helix present in every known CCchemokine structure (6). Mutation of R24 to alanine (R24A) produced the second largest reduction (17-fold) in the interaction with VV-35kDa ( Table 1, Fig.…”
Section: Vv-35kda Contacts Many Of the Same Residues Of Mcp-1 That Con-mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on the IL-8 structure-function relationship suggested that multiple domains of IL-8 are involved in binding and signaling (12)(13)(14). It has been shown that the interaction domains between the inflammatory protein C5a and its receptor consist of two distinct subsites and the occupation of only one of the subsites is required for receptor activation (35).…”
Section: Discussionmentioning
confidence: 99%
“…Results obtained from mutagenesis and synthetic analogs of IL-8 demonstrated that residues Glu 4-Leu 5-Arg 6 of IL-8 were necessary, but not sufficient, for high affinity binding and activities (9 -12). Recent studies identified a second region, comprising residues that cluster near a surface-accessible hydrophobic pocket, that is important for IL-8 function (13,14). This region contains a second site for IL-8 receptor recognition that, in combination with the Glu 4-Leu 5-Arg 6 region, can modulate receptor binding affinity and specificity.…”
mentioning
confidence: 99%